(untitled) (Advances in Military Technology, 2019)
This paper deals with one of the possible methods of a qualified estimation of tactical and technical parameters of surface‐to‐air or air‐to‐air guided missiles. This method is designed to estimate missile flight parameters if they are unavailable from public sources. Although the method does not provide exact values, it is sufficient for modelling and subsequent simulation. This method is based on the use of so‐called “characteristic numbers” of the missile and on the assumption of validity of the hypothesis about the similarity of characteristic missile numbers of equal or, respectively, similar technological levels. To validate the obtained parameters, a method of mathematical modelling of the missile guidance process is used. The method can also be used for a qualified estimation of missile parameters in the case of an acquisition process.